A retrospective cohort analysis of the Yale pediatric genomics discovery program. Issue 10 (28th July 2022) - Al‐Ali, Samir; Jeffries, Lauren; Faustino, E. Vincent S.; Ji, Weizhen; Mis, Emily; Konstantino, Monica; Zerillo, Cynthia; Jiang, Yong‐hui; Spencer‐Manzon, Michele; Bale, Allen; Zhang, Hui; McGlynn, Julie; et al.
Abstract: The Pediatric Genomics Discovery Program (PGDP) at Yale uses next‐generation sequencing (NGS) and translational research to evaluate complex patients with a wide range of phenotypes suspected to have rare genetic diseases. We conducted a retrospective cohort analysis of 356 PGDP probands evaluated between June 2015 and July 2020, querying our database for participant demographics, clinical characteristics, NGS results, and diagnostic and research findings. The three most common phenotypes among the entire studied cohort ( n = 356) were immune system abnormalities ( n = 105, 29%), syndromic or multisystem disease ( n = 103, 29%), and cardiovascular system abnormalities ( n = 62, 17%). Of 216 patients with final classifications, 77 (36%) received new diagnoses and 139 (64%) were undiagnosed; the remaining 140 patients were still actively being investigated. Monogenetic diagnoses were found in 67 (89%); the largest group had variants in known disease genes but with new contributions such as novel variants ( n = 31, 40%) or expanded phenotypes ( n = 14, 18%). Finally, five PGDP diagnoses (8%) were suggestive of novel gene‐to‐phenotype relationships. A broad range of patients can benefit from single subject studies combining NGS and functional molecular analyses. All pediatric providers should consider further genetics evaluations for patients lacking precise molecular diagnoses.